Legal Protection for Consumers in the Transportation Sector: An Analysis of Consumer Rights and the Responsibilities of Public Transport Service Providers - Bernadetta Tjandra Wulandari (Dinasti Research, 2025)
Consumer protection in the transportation sector is a crucial aspect of public service governance, ensuring that consumer rights are safeguarded while maintaining the accountability of service providers. This study aims to analyze the legal protection mechanisms for consumers in the transportation sector, focusing on the rights of consumers and the responsibilities of public transport service providers. Using a qualitative research methodology, this study employs a literature review approach (library research) to examine relevant legal frameworks, regulations, and case studies at both national and international levels. The findings indicate that while many legal frameworks exist to protect consumer rights in the transportation sector, enforcement and implementation remain inconsistent. Consumers are entitled to safety, security, accessibility, and fair treatment, yet challenges such as inadequate regulations, lack of transparency, and insufficient enforcement mechanisms often hinder their protection. Public transport service providers, on the other hand, have a responsibility to ensure service reliability, safety standards, and adherence to consumer protection laws. This study highlights the need for stronger regulatory oversight, improved legal enforcement, and increased consumer awareness to enhance consumer protection in the transportation sector. By analyzing legal principles and international best practices, this study contributes to the discourse on consumer rights and public transport governance. Strengthening legal frameworks and promoting responsible service delivery are essential to ensuring a fair and efficient transportation system.